Multimedia Interaktif berbasis Aplikasi Android untuk Meningkatkan Pemahaman Konsep Mekanika Lagrange Siswa OSN Fisika SMA - Alfi Laily Hidayatul Anisah; Asya Maulida Sakinata (Pendidikan Fisika UIN Alauddin Makassar, 2023)
The learning and training of OSN Physics students in Indonesia is still oriented towards testing students' memory. Meanwhile, there are many OSN Physics questions that require high thinking skills and strong concept understanding, one of which is Lagrange mechanics. This research aims to develop interactive learning media based on android applications that are feasible to use to improve the concept understanding of high school Physics OSN students. The research method used is the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). However, this research only uses the stages of Analysis, Design, Development, and Evaluation. Data collection techniques were carried out with feasibility test sheets of high school physics teacher responses and physics education students using MSI (Method of Successive Interval). The results showed that the Study Lagrange application design is feasible to use to improve the concept understanding of OSN Physics high school students in solving OSN Physics questions that have HOTS question types.